“This Green Red World” by Hrant Matevosyan - Gabrielyan, Vazgen (Bulletin of Yerevan University B: Philology, 2021)
The article attempts to explain and interpret the expression “this green, red world” byHrant Matevosyan as a symbol. To introduce the “Valley – world” which is alive in H.Matevosyan’s literature and is a complete creative work, Nature being the Sun and theSky, earth and water, tree and flower, living and non-living beings, sounds, smells, andcolours, Matevosyan’s worldview of seeing a united world with mutual relations as anexpression of his philosophical, nature-worshipping perception. To demonstrate theMatevosyanean way and principle of particularly "spiritualizing" inanimate and nonspeakingbeings, their “thoughts”, presenting their continuing existence by making it allvisible, audible and tangible: “to write not about a tree, but from within a tree, not abouta horse, but from within a horse”.
Keywords: green red world; homeland; natuive land; Valley-world; nature; living and inanimate beings; creation; humanism; literary relations